But I still don't understand where x = (a * cos t)/(1+sin^2 t) and y = (a * sin t cos t)/(1+sin^2 t) come from.

]]>(x² + y²)² = a² (x² - y²)

It is like this :- ∞

The polar equation is

r²=a²Cos2θ]]>

I'm working on a report in which I have to take the definition of a lemniscate and use it to develop a system of parametric equations to describe it. I know that the most common such system is x = (a * cos t)/(1+sin^2 t) and y = (a * sin t cos t)/(1+sin^2 t).

My question is... how do you derive this from the definition of a lemniscate?

Thanks in advance for any help.

]]>